2010
DOI: 10.1210/en.2009-1023
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte-Derived Microvesicles Are Associated with Multiple Angiogenic Factors and Induce Angiogenesis in Vivo and in Vitro

Abstract: We previously reported that 3T3-L1 and rat primary adipocytes secreted microvesicles, known as adipocyte-derived microvesicles (ADMs). In the present study, we further characterized the 3T3-L1 ADMs and found that they exhibited angiogenic activity in vivo. Antibody arrays and gelatin zymography analyses revealed that several angiogenic and antiangiogenic proteins, including leptin, TNFalpha, acidic fibroblast growth factor (FGFa), interferon-gamma, and matrix metalloprotease (MMP)-2 and MMP-9, were present in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 33 publications
1
41
0
1
Order By: Relevance
“…Many angiogenic factors could be secreted by adipocytes in vitro and in vivo (31). We consistently found that proangiogenic factors, including VEGF, FGF-2, and PlGF, were also secreted by adipocytes in vitro ( Supplementary Fig.…”
Section: The Antiangiogenic Activity Of Endostatin Contributes To Itsmentioning
confidence: 61%
“…Many angiogenic factors could be secreted by adipocytes in vitro and in vivo (31). We consistently found that proangiogenic factors, including VEGF, FGF-2, and PlGF, were also secreted by adipocytes in vitro ( Supplementary Fig.…”
Section: The Antiangiogenic Activity Of Endostatin Contributes To Itsmentioning
confidence: 61%
“…In addition to endothelial and other diseaserelated cells, adipocytes have been recently reported to secrete MPs (58 ). Adipocyte-derived MPs are associated with multiple angiogenic factors and play a role in angiogenesis in adipose tissue.…”
Section: Mps Alter Endothelial Cell Survival and Angiogenesismentioning
confidence: 99%
“…Adipocyte-derived MPs are associated with multiple angiogenic factors and play a role in angiogenesis in adipose tissue. Leptin, tumor necrosis factor-␣ (TNF-␣), and bFGF from adipocyte-derived MPs are involved in endothelial cell migration and tube formation (58 ).…”
Section: Mps Alter Endothelial Cell Survival and Angiogenesismentioning
confidence: 99%
“…Several integral, cytosolic and nuclear proteins such as caveolin-1, c-Src kinase, and heat shock protein 70 were also microvesicle components. Proteomic analysis of the microvesicles revealed that many other proteins, such as extracellular matrix-related proteins (11) and multiple angiogenic factors, were also present (12). The discovery of adipocyte-derived microvesicles might represent a novel component of fat cell biology that must be validated under in vivo conditions.…”
Section: Fat Cell Secretionsmentioning
confidence: 99%